2021
DOI: 10.3389/fpubh.2021.718013
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of the National Centralized Drug Purchasing Pilot Program on Nucleos(t)ide Analogs in Shenzhen City: An Interrupted Time Series Analysis

Abstract: Objectives: To assess the effects of the National Centralized Drug Purchasing Pilot Program on nucleos(t)ide analogs (NAs) in Shenzhen city.Methods: Drugs procurement records in medical institutions were analyzed covering the period from January 2018 to December 2019. An interrupted time series (ITS) analysis was used to evaluate the impact of the “4+7” pilot policy on NAs in Shenzhen city. The outcome measures were usage volume, expenditures, daily cost, and distribution structure of NAs.Findings: After the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 56 publications
(55 reference statements)
1
20
0
Order By: Relevance
“…Most studies found that the volume of policy-related drugs increased, while the purchase spending declined after the implementation of NCDP (4, 16,17). The policy effects on antihypertensive drugs, antibiotic drugs, and nucleoside analogs were consistent with the overall policy effects (18)(19)(20).…”
Section: Introductionmentioning
confidence: 83%
“…Most studies found that the volume of policy-related drugs increased, while the purchase spending declined after the implementation of NCDP (4, 16,17). The policy effects on antihypertensive drugs, antibiotic drugs, and nucleoside analogs were consistent with the overall policy effects (18)(19)(20).…”
Section: Introductionmentioning
confidence: 83%
“… 11 , 17 The growth trend of nationwide data in NAs purchases is supported by a previous report from Shenzhen province. 18 However, that study reported only short-term changes and did not analyze the proportional change of first-line NAs.…”
Section: Discussionmentioning
confidence: 99%
“…Wen et al found that in Shenzhen, the NVBP pilot program was associated with reduced DDDs and improved accessibility of nucleos(t)ide analogs. ( Wen et al, 2021 ). Our study further investigated the impact of the NVBP on antiviral drugs in all pilot cities with a longer period of study time.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several studies have also assessed the effect of NVBP on some specialized drugs, including antibiotics, antihypertensive drugs, and nucleic acid drugs. These studies found that the NVBP might have a positive effect on different types of drugs ( Yang et al, 2021a ; Yang et al, 2021b ; Wen et al, 2021 ). However, the study on the nucleos(t)ide analogs only included the data in one of the pilot cities of the NVBP for a relatively short period of time ( Wen et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation